R*4Tl3Cl and R*6Tl6Cl2 (R*=SitBu3) - the first compounds with larger clusters containing covalently linked Thallium atoms - Wiberg, Nils; Blank, Thomas; Lerner, Hans-Wolfram; Fenske, Dieter; Linti, Gerald W. (Angewandte Chemie. International edition, 2001)
The largest Tl clusters to date with covalently linked Tl atoms are contained in the title compounds obtained from TlCl3 and two molar equivalents of NaSitBu3 in THF at −78°C. The structure of (SitBu3)6Tl6Cl2,...